2002
DOI: 10.1530/eje.0.1470339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose of recombinant human growth hormone on bone metabolism in elderly women with osteoporosis

Abstract: Background: There has been increasing evidence that the growth hormone (GH) -IGF-I axis plays an important part in the maintenance of bone mass. However, controversy still exists as to the effect of GH treatment on bone mineral density (BMD) in elderly patients with osteoporosis. Objective: To investigate the effect of low-dose GH treatment on markers of body composition and bone turnover, serum concentrations of IGF-I and IGF-binding proteins (IGFBPs), and BMD at the radius and lumbar spine in eight elderly J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…The response to GH may differ in diverse clinical situations (ie, hypopituitarism, Shehan syndrome, postmenopause, idiopathic osteoporosis in men, children). 130,132,[154][155][156][157][158][159][160][161][162][163] In an earlier meta-analysis, fluoride, a mineral that is incorporated into bone, increased the risk of fractures when administered in high doses but reduced fractures at low doses. [164][165][166][167][168][169] Fluoride is approved as an osteoporosis therapy in Europe but not in the United States.…”
Section: Antiresorptive Agentsmentioning
confidence: 99%
“…The response to GH may differ in diverse clinical situations (ie, hypopituitarism, Shehan syndrome, postmenopause, idiopathic osteoporosis in men, children). 130,132,[154][155][156][157][158][159][160][161][162][163] In an earlier meta-analysis, fluoride, a mineral that is incorporated into bone, increased the risk of fractures when administered in high doses but reduced fractures at low doses. [164][165][166][167][168][169] Fluoride is approved as an osteoporosis therapy in Europe but not in the United States.…”
Section: Antiresorptive Agentsmentioning
confidence: 99%
“…These studies revealed that agerelated decreases in lean muscle mass, bone mass, immune function, and skin thickness are ameliorated by growth hormone administration (Andersen et al 2000;Davila et al 1987;Rudman et al 1990;Sonntag et al 1985;Sugimoto et al 2002). However, the effects of growth hormone replacement on the aging brain are only beginning to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that GH-IGF-I axis is crucial factor for the maintenance of normal bone mass [14]. However, serum markers for bone remodeling are usually decreased in patients with GH deficiency [15] whereas our patient showed increased turnover of bone metabolism. Otherwise, immobility can also negatively affect a patient's BMD [16].…”
Section: Discussionmentioning
confidence: 49%